Gauging Workplace Readiness: Assessing the Information Needs of Engineering Co-op Students. - Jon Jeffryes; Meghan Lafferty (Issues in Science and Technology Librarianship, 2012)
Librarians at the Science and Engineering Library at the University of Minnesota surveyed engineering students participating in a work placement as part of the cooperative education program. The survey asked about students' on-the-job information usage, comfort level accessing different types of engineering literature, and experience learning to use specific resources. All respondents indicated having to find some sort of information during their work placement. Industry standards and books had particularly high usage. A variety of levels of comfort and history of instruction were also reported. The goal of this study was to get a better idea of the practical information needs that undergraduate engineering students could expect to encounter in the workplace and better tailor our information literacy instruction to meet those needs in the future. These findings will further strengthen our case for curriculum integration in future conversations with engineering faculty. [ABSTRACT FROM AUTHOR]